The development of conjunction use in advanced L2 speech - Jaroszek, Marcin (Studies in Second Language Learning and Teaching, 2011)
The article discusses the results of a longitudinal study of how the use of conjunctions, as an aspect of spoken discourse competence of 13 selected advanced students of English, developed throughout their 3-year English as a foreign language (EFL) tertiary education. The analysis was carried out in relation to a number of variables, including 2 reference levels, one representing English native discourse and the other observed in teacher talk in actual EFL classes, language type exposure, as registered by the participants of the study on a weekly basis, and teaching procedures. The study investigated possible factors determining the development of 3 aspects of conjunction use: (a) formal conjunctions, (b) specific conjunctions, that is, those conjunctions that are both characteristic of natural English discourse and are underrepresented in L2 discourse, and (c) conjunction diversity. The results point to a restricting effect of teacher talk on the development of specific conjunction use and conjunction diversity. These 2 aspects of conjunction use enjoyed only a slight rise, approaching the teacher reference level. On the other hand, formal conjunctions use did increase radically throughout the study, exceeding the native reference level. In this case teacher talk played a reinforcing role at most. As indicated in a correlational analysis, although there was a clear tendency of the participants’ development of conjunction use towards the native reference level, exposure to authentic English may not have been facilitative of the development of this discourse aspect. An interesting observation was made with reference to the effect of formal instruction on the development of conjunction use: Although the subjects did receive intensive training in conjunction use in the 1st semester of their EFL course, it was not until the 2nd year that their levels of formal conjunction use in spoken output increased. This suggests that formal instruction may have no immediate effect on the development of spoken discourse competence.